2019
DOI: 10.1016/j.semcdb.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and tissue repair: What we can learn from planaria

Abstract: Faithful renewal of aging and damaged tissues is central to organismal lifespan. Stem cells (SCs) generate the cellular progeny that replenish adult tissues across the body but this task becomes increasingly compromised over time. The age related decline in SC-mediated tissue maintenance is a multifactorial event that commonly affects genome integrity. The presence of DNA damage in SCs that are under continuous demand to divide poses a great risk for age-related disorders such as cancer. However, performing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 145 publications
(250 reference statements)
3
20
0
Order By: Relevance
“…Nonetheless, we were able to identify three bona fide human PARP homologs involved in DNA dependent functions. We called these DNA dependent PARP homologs Smed-PARP-1, -2, and -3, which is consistent with recent findings [20,22]. Future studies would be required to define the total number of PARP homologs in S. mediterranea.…”
Section: Dna Dependent Parylation Is Evolutionarily Conserved In Schmsupporting
confidence: 85%
See 4 more Smart Citations
“…Nonetheless, we were able to identify three bona fide human PARP homologs involved in DNA dependent functions. We called these DNA dependent PARP homologs Smed-PARP-1, -2, and -3, which is consistent with recent findings [20,22]. Future studies would be required to define the total number of PARP homologs in S. mediterranea.…”
Section: Dna Dependent Parylation Is Evolutionarily Conserved In Schmsupporting
confidence: 85%
“…Recently, we have identified that regeneration requires the activation of the DNA damage response (DDR) [20]. Specifically, we showed that Smed-PARP-3 expression peaks between 0 and 3 hours post-amputation (hpa) and it gradually declines over time, which coincides with an increase in expression 6-12 hpa of other DDR proteins including Smed-PARP-1 and -2 [20]. Extending the analysis during regeneration of anterior Figure 4B).…”
Section: Smed-parp-3 Regulates Cell Death and Neurogenesis During Regmentioning
confidence: 64%
See 3 more Smart Citations